MERLIN - Measuring methane with lidar from space - Feist, Dietrich; Zechlau, Sabrina; Ehret, Gerhard; Bousquet, P. (2024)
Methane is known to be the second largest contributor to greenhouse gas induced warming after carbon dioxide. However, we know much less about its sources and sinks on global to regional scales and their sensitivity to climate change. Emissions of methane from permafrost and from the abundant number of wetlands, lakes, and rivers located in arctic and tropic regions are expected to substantially increase during this century due to the rapid climate warming. Therefore, disentangling natural and anthropogenic methane fluxes is a key scientific task. The French-German Methane Remote Sensing LIDAR Mission MERLIN is designed to measure highly accurate atmospheric columns of methane to identify natural fluxes and emissions to better quantify global and regional sources and sinks, aiming at - reducing uncertainties on the global methane budget. To accomplish this, MERLIN will be relying on its Integrated Path Differential Absorption (IPDA) lidar to access methane atmospheric concentration at all latitudes and in all seasons. Especially, MERLIN will be able to provide spaceborne methane observations also in regions with high cloud cover and at high latitudes in winter time and in the so-called shoulder seasons. The IPDA measurements are insensitive to ground albedo variations and atmospheric aerosol load and will therefore achieve a level of accuracy not possible with the current available passive measurement techniques in space but will provide highly valuable information for closing knowledge gaps concerning global to regional methane distributions. The launch date of the MERLIN satellite is expected in 2029. Here we want to provide an overview of the MERLIN mission together with some discussion on the validation needs.